2016
DOI: 10.1088/1367-2630/18/6/063007
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin relaxation can enhance the performance of a cryptochrome-based magnetic compass sensor

Abstract: The radical pair model of the avian magnetoreceptor relies on long-lived electron spin coherence. Dephasing, resulting from interactions of the spins with their fluctuating environment, is generally assumed to degrade the sensitivity of this compass to the direction of the Earth's magnetic field. Here we argue that certain spin relaxation mechanisms can enhance its performance. We focus on the flavin-tryptophan radical pair in cryptochrome, currently the only candidate magnetoreceptor molecule. Correlation fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 70 publications
2
97
1
Order By: Relevance
“…Furthermore, here we focus on a radical pair state that is formed in a photo-induced electron transfer reaction from the dark-state protein containing the FAD cofactor in the fully oxidized form. It is currently unknown and intensely debated whether this state could form the basis of a magnetic compass [10,12,25,35,43,[76][77][78]. Some evidence in favour of the alternative radical pair resulting from the re-oxidation of the fully reduced cryptochrome by e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, here we focus on a radical pair state that is formed in a photo-induced electron transfer reaction from the dark-state protein containing the FAD cofactor in the fully oxidized form. It is currently unknown and intensely debated whether this state could form the basis of a magnetic compass [10,12,25,35,43,[76][77][78]. Some evidence in favour of the alternative radical pair resulting from the re-oxidation of the fully reduced cryptochrome by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence in favour of the reoxidation hypothesis has become available recently [14,22,[36][37][38][39][40][41]. Furthermore, a suggestion of how to overcome the issue of fast spin relaxation in the superoxide radical anion, which is closely linked to the latter hypothesis, has been provided [42][43]. In any case, here we focus on the photo-reduction, In order to function as magnetic sensor, the radical pair in the cryptochrome must engage in at least two reactive pathways: spin-selective charge recombination, which discriminates the different spin states of the pair, and the competing formation of a signalling state, which induces a cascade of (currently unknown) events eventually giving rise to nervous excitation.…”
Section: Introductionmentioning
confidence: 99%
“…If the radical pair lives much longer than 1 s, spin relaxation destroys the spin coherence and establishes a 1:3 singlet:triplet ratio before the radicals can react. In both cases the effect of a 50 T magnetic field effect is minimal (48)(49)(50). The biphasic character of T  arises from two distinct mechanisms: oscillation of low frequency zero-quantum coherences at small B 0 and energetic isolation of two of the three triplet sub-levels at high B 0 (47,57).…”
Section: Static Magnetic Fieldsmentioning
confidence: 96%
“…To be sensitive to a weak static magnetic field, the coherence must persist for a time comparable to the period of the electron Larmor precession which, in a 50 T magnetic field, is ~700 ns (25). Theoretical treatments often assume negligible spin relaxation during the radical pair lifetime; this is almost always unrealistic (24,(48)(49)(50). The reality is that random molecular motions modulate the local magnetic fields experienced by the electron spins causing irreversible loss of spin coherence.…”
Section: Outlinementioning
confidence: 99%
“…Previous spin chemical models for the avian magnetic compass have either suggested that different reaction products are formed from the different spin-correlated states of the underlying radical pair6, i.e. different singlet and triplet reaction products are expected to emerge and in turn trigger different neurological responses in bird behaviour, or have assumed a model similar to the one presented here222, but without investigating the benefits of a fast spin-dependent regeneration reaction. In both models, the relative yields of the different reaction pathways could be manipulated by reorientation of the radical pair in the magnetic field: the anisotropy of the internal magnetic interactions in the radical pair, i.e.…”
mentioning
confidence: 99%